Methylene blue-mediated hexose monophosphate shunt stimulation in human red blood cells in vitro: independence from intracellular oxidative injury. - Baird, J (1984)
The red blood cell hexose monophosphate shunt (HMS) and proteolytic responses to several concentrations of Methylene Blue or sodium nitrite were measured. The results suggested two distinct mechanisms for activation of the HMS: (1) nitrite treatment increased HMS activity in response to oxidative challenge to red cell protein; (2) Methylene Blue treatment activated HMS without injurious oxidative challenge. Nitrite-treated cells actively degraded protein, whereas Methylene Blue-treated red cells did not activate proteolytic systems that degrade oxidized red cell protein. These observations are relevant to proposed in vitro systems for evaluation of drug hemolytic toxicity potential on the basis of HMS stimulation capacity.